The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1051/alr:2005018
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, catch composition and CPUE of the artisanally harvested mangrove crabUcides cordatus(Ocypodidae) in the Caeté estuary, North Brazil: Indications for overfishing?

Abstract: -To evaluate the population structure of Ucides cordatus in the Caeté estuary, crabs were sampled bimonthly over 13 months in three Rhizophora mangle forest stands that differed in their accessibility and fishing history. Additionally, sex-and size composition of the commercial catch and catch per unit of effort (CPUE -the number of crabs captured per fisherman per day) were monitored between 1997 and 2003. Average and maximum crab sizes (carapace width, CW) from all three sampling sites combined were 6.1 cm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
110
7
15

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(152 citation statements)
references
References 24 publications
12
110
7
15
Order By: Relevance
“…In many regions of Brazil crabs are threatened by habitat destruction, diseases and fishery (Nordi, 1994;Botelho et al;2000, Alves et al, 2005Boeger et al, 2005). In our study area, 320 km southeast of the Amazon mouth, the local Ucides population is still comparably healthy (Glaser and Diele, 2004;Diele et al, 2005), but fishing pressure is increasing due to demographic growth and adequate management strategies are currently being discussed.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In many regions of Brazil crabs are threatened by habitat destruction, diseases and fishery (Nordi, 1994;Botelho et al;2000, Alves et al, 2005Boeger et al, 2005). In our study area, 320 km southeast of the Amazon mouth, the local Ucides population is still comparably healthy (Glaser and Diele, 2004;Diele et al, 2005), but fishing pressure is increasing due to demographic growth and adequate management strategies are currently being discussed.…”
Section: Introductionmentioning
confidence: 81%
“…Approximately 140 km² of the Caeté peninsula is covered with mature mangrove forests densely populated by crabs, Ucides cordatus and fiddler crabs (Uca spp.) being the most abundant ones (Koch and Wolff, 2002;Diele et al, 2005;Koch et al, 2005). The region is characterized by semidiurnal macro tides with up to 5 m amplitude during the spring tide period.…”
Section: Study Area and Field Measurementsmentioning
confidence: 99%
“…Conhecido popularmente como caranguejouçá, pode atingir grande porte, sendo explorado em várias regiões brasileiras, onde serve como fonte de alimento e renda para populações ribeirinhas (RODRIGUES et al, 2000;PASSOS & DI BENEDITO, 2005;JANKOWSKY et al, 2006). Apesar de sua importância sócio-econômica, só recentemente tem-se notado um incremento das investigações sobre sua bioecologia (BRANCO, 1993;BOTELHO et al, 1999;IVO et al, 1999IVO et al, , 2000PINHEIRO & FISCARELLI, 2001;ALVES & NISHIDA, 2004;MONTEIRO & COELHO-FILHO, 2004;DIELE et al, 2005;PINHEIRO & HATTORI, 2006;ANDRADE et al, 2007;WUNDERLICH et al, 2008;ARAÚJO & CALADO, 2009), como também por aspectos sociais, econômicos, culturais e ecológicos relacionados a sua pesca (MANESCHY, 1993;NORDI, 1994;FISCARELLI & PINHEIRO, 2002;SOUTO, 2007). Com relação à determinação do tamanho da maturidade sexual que tenha levado em consideração tanto a maturidade morfológica como a fisiológica, somente um estudo foi desenvolvido por PINHEIRO & FISCARELLI (2001) até a presente data, mas para uma população do litoral de São Paulo.…”
unclassified
“…In the northeast (Diele et al 2005, Diele andKoch 2010) and southern (Dalabona and Silva 2005) regions of Brazil, the reproduction of the mangrove crab U. cordatus is closely associated with the rainy season, similar to that of other semi-terrestrial crabs (Crane 1943, Haley 1972, Henmi 1989, Henmi and Kaneto 1989, Debelius 1999. According to Nascimento (1993), U. cordatus migrates once a year, when the individuals leave their burrows and travel to the sea where they copulate and release their larvae.…”
Section: Introductionmentioning
confidence: 80%
“…Fiscarelli and Pinheiro (2002), working at Iguape, São Paulo, reported that U. cordatus performs two types of "andada": one for mating and the other for larval release. Diele et al (2005) and Góes et al (2000) mentioned that the "andada" of U. cordatus occurs on the first days of the full and new moon periods, in synchrony with the wider tidal amplitudes. Further details about the "andada" were recorded by Góes et al (2000), although they did not quantify this event or evaluate its dynamics or association with environmental factors.…”
Section: Introductionmentioning
confidence: 98%